Siaka, an African Musician, 80 minutes, DVD. An African Brass Band, 72 minutes, DVD. Author and Producer-Director: Hugo Zemp - McConnachie, Boudina (International Library of African Music, 2008)
pages: 125-127
Keywords: African Music